The Association among Difficulties in Emotion Regulation, Hostility, and Empathy in a Sample of Young Italian Adults - Contardi, Anna; Imperatori, Claudio; Penzo, Ilaria; Del Gatto, Claudia; Farina, Benedetto (Frontiers in Psychology, 2016)
The aim of the present study was to assess the role of empathy in mediating the association between difficulties in emotion regulation and hostility. 360 young Italian adults (220 women and 140 men) were enrolled in the study. Psychopathological assessments included the Difficulties in Emotion Regulation Scale (DERS), the Interpersonal Reactivity Index (IRI) and the Buss-Durkee Hostility Inventory (BDHI). Perspective taking (PT) and Personal distress (PD) are significantly associated with both DERS total score and BDHI total score. A mediational model analyzing the direct and indirect effects of DERS on BDHI through the mediating role of PT and PD showed that the relation between DERS and BDHI was partially mediated by PT total score (b = 0.16; se = 0.01; p = 0.02). Taken together our findings support the possibility that perspective taking skills could play a crucial role in inhibiting hostility behaviors.